Talent Management Strategy in Retaining the Millennial Generation - Qasabandiyah, Muhammad Kholidinna; Farida, Umi (YUME : Journal of Management, 2024)
This study examines the talent management strategies essential for retaining the millennial generation in the workforce. As millennials (individuals born between 1981 and 1996) increasingly comprise a significant portion of the labor market, understanding their unique motivations and preferences is crucial for organizations seeking to enhance employee retention and engagement. The research explores key elements that influence millennial retention, including flexible work arrangements, opportunities for career development, recognition programs, and a commitment to diversity and inclusion. Utilizing established theoretical frameworks such as Maslow’s Hierarchy of Needs, Herzberg’s Two-Factor Theory, and Social Exchange Theory, the study identifies effective strategies that align organizational practices with millennial values.Results indicate that organizations implementing tailored talent management strategies experience improved retention rates, higher employee engagement scores, and a stronger employer brand. The findings highlight the importance of fostering a supportive work environment that prioritizes work-life balance, continuous learning, and meaningful work experiences. Additionally, recommendations are provided for organizations to enhance their talent management practices, including the development of comprehensive onboarding programs, structured feedback mechanisms, and personalized career development plans.This research contributes to the understanding of millennial workforce dynamics and offers valuable insights for organizations aiming to create an inclusive and engaging workplace culture. Future research directions are suggested to further explore the impact of evolving workplace trends on millennial retention strategies. Keywords: Talent Management, Effectiveness, Employee Retention, Career Development